Genetic variation in three candidate genes and nicotine dependence, withdrawal and smoking cessation in hospitalized patients. (August 2010) - De Ruyck, Kim; Nackaerts, Kristiaan; Beels, Laurence; Werbrouck, Joke; De Volder, Annick; Meysman, Marc; Salhi, Bihiyga; Van Meerbeeck, Jan; Thierens, Hubert
Aims: This study evaluates the relationship of six polymorphisms found in the CHRNA3, DRD2 and COMT genes with nicotine dependence, the ability to quit smoking and the occurrence of withdrawal symptoms after short-term use of nicotine patch in hospitalized patients.Materials & methods: The study included 233 participants from a double-blind, placebo-controlled trial of nicotine patch substitution with a 6-month follow-up period. Nicotine dependence was assessed by the Fagerström Test for Nicotine Dependence (FTND) questionnaire, withdrawal symptoms by the Minnesota Nicotine Withdrawal Scale questionnaire and smoking cessation by self-reported abstinence at 1 week, 1 month and 6 months after treatment.Results: After correcting for multiple testing, three polymorphisms in the DRD2 gene (Taq1A, Taq1B and Pro319Pro) were significantly associated with nicotine dependence (p = 0.018, p = 0.048 and p = 0.006, respectively). Using a cutoff point for the FTND score, the CHRNA3 Tyr215Tyr (rs1051730) polymorphism was also associated with nicotine dependence (p = 0.037 and p = 0.074 after correction for multiple testing). No association of any of the studied polymorphisms was observed with either smoking cessation or the occurrence of withdrawal symptoms.Conclusion: This study confirms the reported association of the CHRNA3 locus with nicotine dependence and shows the involvement of two independent DRD2 polymorphisms in nicotine dependence.